Caracterização imuno-histoquímica e molecular de equídeos naturalmente infectados pelo vírus da anemia infecciosa equina - Bruna Lopes Bueno (2019)
Equine infectious anemia (EIA), a disease caused by Equine infectious anemia virus (EIAV), is considered an obstacle to the development of horse industry. EIAV is transmitted by hematophagous insects mainly of the Tabanidae family and also iatrogenicaly. EIA has no treatment or vaccine and pathogenesis, as well as immune response against the virus are not fully understood. Also, the performance of laboratorial diagnosis by serological tests can be poor or limited. In this sense, the immunohistochemistry method has been used to enhance the knowledge about tropism and pathogenicity of several infectious agentes, such as viruses. Therefore, the objective of this work was the development of an immunohistochemical assay for detection of viral antigens in tissues and organs of naturally EIAV infected equids. Fragments of organs of equids (n=6) from Apodi – RN, Brazil, diagnosed as positive for EIA by serological tests were fixed in 10% buffered formalin and paraffin-embedded. Histological sections were collected on polarized slides and antigenicity recovered by heat, using citrate buffer (pH=6). These sections were incubated with polyclonal antibody overnight, and later, with peroxidase-conjugated secondary antibody (Sigma – Aldrich) for 50 minutes. Antigen/antibody reaction was revealed with the ImmPACT™ DAB Peroxidase Substrate (Vector Laboratories) kit counterstained with hematoxylin (Sigma-Aldrich). EIAV antigens were observed in intracytoplasmic region of spleen, liver, kidneys and lungs cells. Immunohistochemical marks were present mainly in red pulp of the spleen, a region with plenty of macrophages, and in hepatic sinusoids, where Kupffer cells (liver macrophages) lies. In addition, marks were found in bronchiolar epithelium and alveolar septum, as well as in epithelium of distal and proximal tubule of kidneys. The highest amount of EIAV was observed in spleen and liver, sites normally full of macrophages, confirming viral tropism to the mononuclear phagocytes. However, presence of EIAV in epithelial cells of lungs and kidneys indicates that the virus may also infect other types of cells besides macrophages, making possible elimination of virus in urine and in oronasal secretions, and facilitating new transmission mechanisms that must be investigated.